Perkembangan Sistem Informasi Akuntansi Melalui Pemanfaatan Teknologi pada Pt. Prodia Diacro Laboratories - Bayu Pratama (Jurnal Ekonomi, 2017)
The use of information technology for problem-solving approach associated with accounting will be able to simplify the processes - processes associated with the processing of information data, in this case the accounting transactions. Problem solving approach using accounting information system using hardware (hardware) in the form of computer devices, and using software (software) that is applications that support an accounting information system itself.The current emerging technology in PT. Prodia Diacro Laboratories plays a major role in accounting information systems. The use of information technology systems in accounting information systems include information system functions, end-user computing (end user computing), and rapid response technology. Development of accounting information systems are professionally conducted both internally and externally. Acumatica System The Cloud ERP that is in use PT. Prodia Diacro Laboratories can minimize weakness.